Agreement between ultrasonography and histopatologic findings in diagnosing retinoblastoma - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Retinoblastoma is a rare eye tumor of childhood that represents the most common intraocular malignancy of infancy and childhood. Diagnosis of retinoblastoma are based on ophthalmological examination and imaging, including ultrasonography (USG). In a typical case of retinoblastoma, it will provide a nearly Rathognomonic picture with cottagecheese calcification, with density higher than the sclera and high internal reflectivity in USG findings. Histopathologic examination is a gold standard for malignany cases and Flexner-Wintersteiner cells is a pathognomonic sign. The aim of this study is to determine the value of an agreement test comparing USG as a preoperative diagnostic tool with histopatologic examination in diagnosing retinoblastoma. This study was an observational agreement test. All of the patients with clinically suspected intraocular lession were examined with USG followed by surgery and histopathologic examination in Eye Clinic of Dr. Sardjito Hospital, Yogyakarta. The result of USG examinations was interpreted by one eye oncologist and the histopathologic reading was performed by one anatomical pathologist. Data were analyzed to determine the agreement value. Thirty three eyes, 21 eyes were retinoblastoma suspected and 12 eyes were nonretinoblastoma suspected based on USG examination), were observed in this study. One eye (3.03%) was false positive case and 1 was false negative case. The Kappa value of agreement test was 0.87. In conclusion, ultrasonography of the eye as a pre-operative diagnostic tool had an excellent agreement compared with histopathological examination as a gold standard in retinoblastoma.